Implementing the Interpretation of Article 121 Paragraph (3) of the UNCLOS Conducted by The Permanent Court of Arbitration towards Sekatung Island as a Maritime Feature in Indonesia-Vietnam’s Maritime Delimitation Negotiation - Btariany Anindita (Padjadjaran Journal of International Law, 2022)
Indonesia’s government is conducting a maritime delimitation negotiation with Vietnam since 2021 discussing the delimitation of the EEZ. According to a method of delimitation, determining the status of a maritime feature is one of many vital points to be discussed during a delimitation negotiation. Sekatung Island, a small island belongs to Indonesia, which located between Indonesia and Vietnam has a vital part to determine the width of Indonesia’s EEZ. Article 121 paragraph (3) of the UNCLOS is the main legal basis to determine the legal status of Sekatung Island. Aforementioned Article has been interpreted by the Permanent Court of Arbitration in the South China Sea Arbitral Award. In summary, the PCA declared maritime features must have the natural capacity to sustain human habitation and economic life of their own, based on historic evidences, in order to determine such features as fully entitled island with up to 200 nautical miles of EEZ and continental shelf. The purpose of this article is to give a point of view for Indonesia’s government regarding the deficiency of such interpretation by the PCA which may leads to disadvantaging Indonesia’s position during delimitation negotiation, if in any case the government would implement such interpretation to determine the legal status of Sekatung Island. Keywords: South China Sea Arbitral Award, Rocks, UNCLOS, maritime delimitation